Kyrgyz Republic : Medium-Term Development Program: Poverty Reduction Strategy Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This paper focuses on the Medium-Term Development Program for the Kyrgyz Republic. The aim of this program is to put the economy of the country into a sustainable vector of development and improve the budget status to prevent social effects, increase living standard, and reduce poverty in the country. Implementation of the reforms anticipated by the Program will help to reduce the State budget deficit, enhance the fight against corruption, improve living standards, and decrease social tension in the society.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet